Two Novel 30K Proteins Overexpressed in Baculovirus System and Their Antiapoptotic Effect in Insect and Mammalian Cells - Wei Yu; Qing Li; Yuhua Yao; Yanping Quan; Yaozhou Zhang (International Journal of Genomics)
The 30K family of proteins is important in energy metabolism and may play a role in inhibiting cellular apoptosis in silkworms (Bombyx mori). Several 30K-family proteins have been identified. In this study, two new silkworm genes, referred to as Slp (NM 001126256) and Lsp-t (NM 001043443), were analyzed by a bioinformatics approach according to the sequences of 30K proteins previously reported in the silkworm. Both Slp and Lsp-t shared more than 41% amino acid sequence homology with the reported 30K proteins and displayed a conserved domain consistent with that of lipoprotein-11. Additionally, the cDNA sequences of both Slp and Lsp-t were obtained from the fat bodies of silkworm larvae by reverse transcription polymerase chain reaction. Both genes were expressed in BmN cells using the Bac-to-Bac system. Purified Slp and Lsp-t were added to cultured BmN and human umbilical vein endothelial cells (HUVEC) that were treated with H2O2. Both Slp and Lsp-t significantly enhanced the viability and suppressed DNA fragmentation in H2O2 treated BmN and HUVEC cells. This study suggested that Slp and Lsp-t exhibit similar biological activities as their known 30K-protein counterparts and mediate an inhibitory effect against H2O2-induced apoptosis.